Psychometric evaluation of the Spanish version of the Pediatric Quality of Life Eosinophilic Esophagitis Questionnaire (Peds QL-EoE Module ™) - Ruth Garcia – Martinez de Bartolomé; Josefa Barrio-Torres; MLuz Cilleruelo- Pascual; Juan José Rodríguez-Soler; Ángel Gil-de Miguel; Tomás Sebastián-Viana; the Spanish Study Group of Children’s Eosinophilic Esophagitis Quality of Life (Health and Quality of Life Outcomes, 2023)
Abstract Background The Paediatric Eosinophilic Oesophagitis Module (PedsQL-EoE) was developed in English as a valid and reliable questionnaire to assess health-related quality of life (HRQoL) in children with EoE. The aim of this study was to evaluate the validity and reliability of the PedsQL-EoE that was previously adapted to Spanish by our group. Methods This cross-sectional multicentre study was conducted in 36 paediatric gastroenterology units. Groups with and without dietary restrictions were studied separately. The PedsQL-EoE consists of 33 items divided into seven factors. Age-specific versions of the PedsQL-EoE were sent by e-mail to children and parents. Statistical analysis was used to study the questionnaire structure by means of exploratory factor analysis and interitem correlations. Confirmatory factor analysis (CFA) was applied to verify the proposed model as well as its psychometric properties through SMSR (standardized root mean square), outer loadings and R-square. To study construct validity and reliability, Cronbach´s alpha coefficient, convergent validity (AVE), discriminant validity (HTMT) and intraclass correlation coefficients (ICC) were used. Results A total of 341 children and 394 parents participated with 307 matched answers. The median age was 12 years, and 75% were male. The questionnaire structure explained 68% and 66% of the total variance for parents and children, respectively. Five items showed negative correlations and were removed from the questionnaire. CFA applied to the new model supported the following construct: SMRS was less than 0.08, outer loadings measured above 0.5, and R2 explained more than 89% of the total variance. Once the modifications were performed, good internal consistency was demonstrated, with Cronbach’s alpha values > 0.7, AVE values > 0.5 and HTMT < 0.9 with good child/parent agreement (ICC = 0.80). The most robust model of the PedsQL-EoE module was formed by seven factors: Symptoms I (6 items), Symptoms II (4 items), Treatment (4 items), Worries (3 items), Communication (5 items), Food and Eating (3 items) and Food Feelings (3 items). Conclusions The final PedsQL-EoE Module version, after the removal of five items, is a valid and reliable tool to be used in children with EoE. The Spanish validated version appears to be a useful instrument for measuring the impact of EoE on Spanish children´s quality of life.